Using Linkage Maps as a Tool To Determine Patterns of Chromosome Synteny in the Genus Salvelinus. Issue 11 (1st November 2017) - Hale, Matthew C; McKinney, Garrett J; Bell, Courtney L; Nichols, Krista M
Abstract: Next generation sequencing techniques have revolutionized the collection of genome and transcriptome data from nonmodel organisms. This manuscript details the application of restriction site-associated DNA sequencing (RADseq) to generate a marker-dense genetic map for Brook Trout ( Salvelinus fontinalis ). The consensus map was constructed from three full-sib families totaling 176 F1 individuals. The map consisted of 42 linkage groups with a total female map size of 2502.5 cM, and a total male map size of 1863.8 cM. Synteny was confirmed with Atlantic Salmon for 38 linkage groups, with Rainbow Trout for 37 linkage groups, Arctic Char for 36 linkage groups, and with a previously published Brook Trout linkage map for 39 linkage groups. Comparative mapping confirmed the presence of 8 metacentric and 34 acrocentric chromosomes in Brook Trout. Six metacentric chromosomes seem to be conserved with Arctic Char suggesting there have been at least two species-specific fusion and fission events within the genus Salvelinus . In addition, the sex marker ( sdY ; sexually dimorphic on the Y chromosome) was mapped to Brook Trout BC35, which is homologous with Atlantic Salmon Ssa09qa, Rainbow Trout Omy25, and Arctic Char AC04q. Ultimately, this linkage map will be a useful resource for studies on the genome organization of Salvelinus, and facilitates comparisons of the Salvelinus genome with Salmo and Oncorhynchus .